Népi vallásosság komplementer vallásosság - Cserbák András; Szentemberek - a vallásos élet szervező egyéniségei (1992) (Szeged) (1998)
In the Hungarian ethnography of religion besides the everyday work there are two unsolved theoretical questions. On the one hand the scholars of the ethnography of religion should free themselves from a hidden critique of religion, that manifests itself in confrontating folk religiousness and professional religousness in allusions or openly. It isn't an excellent idea if scholars qualify folk religiousness always positively, and the church professional religiousness always negatively, this way overstepping the mark of the compulsory neutrality of competence, or professional objectiveness. It is nearer the thruth, if the two kinds of religiousness are complementarily interpreted as an integral whole. It seems to be an urgent thing to extend systematical approximation to an other field of the ethnography of religion. In the European ethnography there is an ambition to study the phenomena of folk religiousness, the folk beliefs, religious customs and of healing with religious actsin the complex system of religious ethnology, on the evidence of the religious elements. The principle of interdisciplinity is also operative inside the same science, and admitting the results of more and more special studies, we must consider at lest the same level the results of seizing and interpreting phenoena in their complexity and systematic inherences. This complex method is especially suitable for examining the special organizer personalities of the folk religiousness or the clairvoyants of singular abilities, as their personal attractiveness have sometimes extended overseveralregions. Consequently, the geographical environment itself is extremely complex, where uncommon phenomena must be seized, studied and interpreted. So the complexity of the unresolved problems and the complexity of processing results makes necessary the use of the interdisciplinary teamwork and the technical advantages of the computers.
Keywords: Társadalomtudományok; Szociológia